VLSI fabrication principles: Silicon and Gallium Arsenide - Ghandhi, Sorab K. (New Delhi: John Wiley & Sons, 1994)
Fully updated with the latest technologies, this edition covers the fundamental principles underlying fabrication processes for semiconductor devices along with integrated circuits made from silicon and gallium arsenide. Stresses fabrication criteria for such circuits as CMOS, bipolar, MOS, FET, etc. These diverse technologies are introduced separately and then consolidated into complete circuits. An Instructor's Manual presenting detailed solutions to all the problems in the book is available from the Wiley editorial department.
Material Properties -- Phase Diagrams and Solid Solubility -- Crystal Growth and Doping -- Diffusion -- Epitaxy -- Ion Implantation -- Native Films -- Deposited Films -- Etching and Cleaning -- Lithographic Processes -- Device and Circuit Fabrication -- The Mathematics of Diffusion
Includes bibliography and index